2019
DOI: 10.3389/fcimb.2019.00205
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Oral Microbiota Composition Are Associated With a Risk of Throat Cancer

Abstract: In this study, a next-generation sequencing strategy on 16 S ribosomal RNA (16 S rRNA) gene was employed to analyze 70 oral samples from 32 patients with throat cancer, nine patients with vocal cord polyp, and 29 healthy individuals (normal controls). Using this strategy, we demonstrated, for the first time, that the salivary microbiota of cancer patients were significantly different from those of patients with a polyp and healthy individuals. We observed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 61 publications
3
32
2
Order By: Relevance
“…On the other hand, gastrointestinal cancers of various origins were associated with an increased salivary bacterial diversity and high levels of P. gingivalis as compared to matched healthy controls [83]. In line, a study from 2019 used NGS of SM to discriminate patients with throat cancer from healthy controls and patients with vocal cord polyps with an AUC = 0.87 [84]. Finally, two cross-sectional studies have compared SM in patients with lung cancer to healthy controls.…”
Section: Cancermentioning
confidence: 98%
“…On the other hand, gastrointestinal cancers of various origins were associated with an increased salivary bacterial diversity and high levels of P. gingivalis as compared to matched healthy controls [83]. In line, a study from 2019 used NGS of SM to discriminate patients with throat cancer from healthy controls and patients with vocal cord polyps with an AUC = 0.87 [84]. Finally, two cross-sectional studies have compared SM in patients with lung cancer to healthy controls.…”
Section: Cancermentioning
confidence: 98%
“…Researchers in northeast China used receiving operational curve (ROC) analysis on the putative throat cancer markers Pseudomonas, Aggregatibacter, Bacteroides, and Ruminiclostridium6, and they found robust diagnostic accuracy with an area under the curve (AUC) of 0.875. These results indicated that specific oral microorganisms might be promising noninvasive biomarkers for making an early detection and diagnosis of cancer patients (Zhu et al, 2017;Lim et al, 2018;Wang et al, 2019). However, influence from geographical factors, races and ethnicities, dietary habits, and climates may affect the oral microbial profiles of local people (He et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…These studies have demonstrated that the mucosal layers of the mouth, throat, stomach, and intestines are colonized by commensal bacteria, which play an important part in normal human health and can therefore also play a role in the development of malignancies. For example, Helicobacter pylori infection can induce gastric cancer through gastric dysbiosis (63).…”
Section: Microbiomicsmentioning
confidence: 99%
“…The association between variations in the human microbiome and throat cancer has also been studied. Wang et al studied microbial markers in the saliva of patients with throat cancer (hypopharyngeal carcinoma and laryngeal carcinoma) and in the saliva of patients with vocal cord polyps and healthy controls (63). They revealed a significant difference in the microbiome of throat cancer patients vs. patients with vocal cord polyps and healthy controls.…”
Section: Microbiomicsmentioning
confidence: 99%